Abundance and Diversity of Diatom Class Bacillariophyceae as Bioindictaor of Pollution in the Waters of Tanjung Luar Fish Landing Based - Niswatul Audah; Lalu Japa; M. Yamin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Tanjung Luar is coastal water used as a waste disposal area for Fish Landing Based (FLB) activities. However, the condition of the waters with phytoplankton as a bioindicator has never been reporting. This research aims to know Bacillariophyceae in terms of abundance, diversity, and measurement of environmental pollution variables. Methods Sampling at the study location was determined by a systematic random sampling method. Data analysis Bacillariophyceae were determined using formula abundance, diversity index, and dominance index. The index of similarity of species between sample points was determined based on the Bray-Curtis Cluster Analysis. Furthermore, the results showed an abundance of Bacillaryophyceae of 322,000 individuals / L classified as low, the diversity index of Bacillariophyceae of 2.162 classified as moderate, and a dominance index of 0.138 (without dominating species). The results showed that the highest species similarity index was between sample points II and III (57.9%), and the lowest species similarity index between sample points I and II was 23.7%. Water pollution on the waters of PPI Tanjung Luar is classified as moderate pollution level and oligotrophic fertility.